2004
DOI: 10.1088/0741-3335/46/5/010
|View full text |Cite
|
Sign up to set email alerts
|

Finite ion Larmour radius effects in the problem of zonal flow generation by kinetic drift-Alfvén turbulence

Abstract: A theory of spontaneous generation of zonal flows by kinetic drift-Alfvén turbulence in the finite-pressure plasma (β > m e /m i ) is generalized to include the ion diamagnetic effects and the finite ion Larmour radius effects. In the framework of the corresponding set of generalized two-fluid magnetohydrodynamic equations and on the assumption of a distinct time-and space-scale separation between the turbulent oscillations and the zonal flow, a set of coupled equations is derived to describe the interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…An analysis of the role of additional physical effects can be the topic of following studies; see also Ref. 18. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the role of additional physical effects can be the topic of following studies; see also Ref. 18. …”
Section: Discussionmentioning
confidence: 99%
“…14 An important contribution to the nonlinear theory of SSDA modes was the investigation of zonal flows generated by them, carried out originally by Smolyakov et al 17 and later continued by Lakhin. 18 The theory presented in Ref. 17 is particularly relevant because it develops the basic mathematical framework to describe the generation of zonal flows in two distinct approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason that zonal flows driven by drift-type turbulence have been intensively investigated theoretically in recent years. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Another reason for the investigation carried out in the given paper are the results obtained by Kaladze et al 86 In that paper it was shown that in EPI plasma three different types of nonlinear solitary vortical structures on the electrostatic drift waves can appear. ͑1͒ Short-scale vortical structures of dipole type stipulated by the vector nonlinearity only.…”
Section: Generation Of Zonal Flows By Electrostatic Drift Waves In Elmentioning
confidence: 82%
“…[25][26][27][28] Such turbulence can also drive lower frequency modes, in particular the zero-frequency CCs. 29,30 To study the interaction between the CCs and the KAW turbulence, it is convenient to use the wave kinetic equation for the generalized KAW action and the hydrodynamic equations for the CCs since their dynamics involve quite different time and space scales. 14,31 References 29 and 30 considered the coupling of CCs with KAW turbulence for intermediate b plasmas, as in the auroral zone at geocentric distances above 5R E , 32 where R E is the Earth's radius.…”
Section: Introductionmentioning
confidence: 99%